Applicability of oxygen scavengers for shelf life extension during illuminated storage of cured cooked meat products packaged under modified atmosphere in materials with high and low oxygen permeability. Issue 3 (19th December 2020) - Baele, Maarten; Vermeulen, An; Leloup, Frédéric B.; Adons, Dimitri; Peeters, Roos; Devlieghere, Frank; De Meulenaer, Bruno; Ragaert, Peter
Abstract : The aim of this study was to evaluate the effect of illumination, packaging material and application of oxygen scavengers on the shelf life of two different cured cooked meat products in diverse retail storage conditions. For this purpose, ham luncheon sausage and pork liver pâté were packaged in high‐ and low‐OTR (oxygen transmission rate) packages under modified atmosphere. Packages either did or did not contain a 50‐ml O2 capacity oxygen scavenger. Samples were stored at 7°C either in complete darkness or illuminated by fluorescent or LED lamps for the last 48 h of storage. Microbial quality of pâté was more crucial than that of ham sausage, partially due to a higher initial microbial load. Pâté was far more susceptible to discolouration and lipid oxidation than ham luncheon sausage. Illumination was a crucial aspect for discolouration of ham sausage, whereas pâté exhibited discolouration without illumination when packaged in low barrier packages. Hence, high barrier packages are indispensable for these types of products, especially pâté. Inclusion of an oxygen scavenger may lead to improved colour stability and lower lipid oxidation, provided that the packaging material had a sufficiently low OTR and some days of dark storage preceded illumination. Replacing a multilayered high‐barrier packaging system with a lower barrier system with an added scavenger is not an interesting option as there is competition for oxygen absorption between the food product and the scavenger. Abstract : Two types of cured cooked meats were packaged in high‐ and low‐OTR packages, either with or without an oxygen scavenging sticker. The samples were stored at 7°C either in complete darkness or illuminated by fluorescent or LED lamps for the last 48 h of storage. Inclusion of an oxygen scavenger may lead to improved colour stability and lower lipid oxidation, provided that the packaging material had a sufficiently low OTR and some days of dark storage preceded illumination.